Nicho trófico e aspectos bionômicos da abelha solitária Tetrapedia diversipes KLUG (Hymenoptera, Apidae, Tetrapediini) - Cavalcante, Arianne Moreira (2016)
In the world, there are more than 20,000 species of bees described. Among them there are the solitary bees Tetrapedia diversipes, belonging to Tetrapediini tribe, which occur exclusively in the Neotropics. T. diversipes. The females, as well as males, have morphological and behavioral adaptations that allow the collection of floral lipids used by females in feeding larvae, in the construction of brood cells and sealing of the nests. These bees have varied nesting habits, for ground-nesting in termitaria or pre-existing cavities in wood, enabling the use of trap nests in the study areas. This method allows to obtain information about the nesting behavior, nest architecture and resources provided to the larvae. All this knowledge provides grants for studies on environmental requirements of these bees, as well as for the development of management techniques for the maintenance of these native bees in the environment. In this sense, the objective of this study was to bionomics of Tetrapedia diversipes and identify the plant species used in the diet of their immature, through cropopalinologica analysis. The study was conducted at the Federal University of Ceará Bees industry in the period between December 2014 and September 2015 by providing trap nests made of black paper and straws transparent plastic. During the study were recorded 135 nests where the highest percentage of Nest establishment occurred at the end of the rainy season and early dry season, but there was no significant difference between the monthly nesting rate (%) and evaluated climate variables: temperature (° C) r = -0.1635; p = 0.6517; relative humidity (%) r = 0.4954; p = 0.1454 and rainfall (mm) r = 0.4285; p = 0.2166. The number of cells creates constructed by these bees in each nest ranged from 1 to 8, a total of 593 cells. In these nests emerged 297 females, 151 males and two individuals parasitic species. The Tetrapedia diversipes females used resources of 29 plant species to feed their offspring. The pollen type with the largest representation in the diet of these bees was Dalechampia sp. (Euphorbiaceae) composing 59.57% of all analyzed pollen. The specific analysis of stool present in males cells (n = 31) and female (n = 66) revealed that the diet of male pollen is composed of more types than diet females. However, when compared with the amplitude of the trophic niche between the two sexes, males had a less diverse diet compared to females (H'F = 1:32; H'F = 8.1; t = 16,371; p <0.0001). The studied also indicated that there was a strong overlap in the use of plants as pollen source of 98.9% (CH = 0.989) between the two sexes, but there was no statistical difference in the frequency distribution of the food items of males and females (D = 0.214; p = 0.341). The pollen types Dalechampia sp (Euphorbiaceae) and Talinum triangulare (Portulacaceae) were more frequent in both diet of females as males in the diet. This study showed that T. diversipes both built their nests in the rainy season and the dry season has low levels of parasitism. The results of stool samples of these bees showed that the diet is rich in immature different pollen types indicating that this species is polilética.